A turnpike theorem for continuous-time control systems when the optimal stationary point is not unique. (16th June 2003) - Mamedov, Musa A.
Abstract : We study the turnpike property for the nonconvex optimal control problems described by the differential inclusionx ˙ ∈ a ( x ) . We study the infinite horizon problem of maximizing the functional∫ 0 T u ( x ( t ) ) d t asT grows to infinity. The turnpike theorem is proved for the case when a turnpike set consists of several optimal stationary points.